Essays in applied economics - Pigou, A. C. (London. Frank Cass & Co. Ltd, 1965)
This book consist of sixteen essays, mainly reprinted from the Economic journal, the Contemporary review, the Quarterly journal of economics, and other periodicals on applied economics.
Include footnotes.
osa 22/01/19
Loans
Keywords: Economics; Wages; Great Britain